SURGICAL PATHOLOGY AND SACCHARINE DIABETES - Шевчук, А. Г.; Боцюрко, В. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
In work the question is saccharine diabetes, as a surgical problem, in four aspects: - at the sharp surgical diseases of organs of abdominal and pectoral region, buds, nagniynih defeats of skin and hypodermic cellulose; - for appearances of clinic of sharp stomach; - for injuring of separate organs; - at the chronic diseases of organs and systems, which require the methods of operative medical treatment.